Comparison of frequency of seroma formation in laparoscopic para umbilical hernia repair with and without primary closure of defect - Khan, Shamin; Maryam Siddiqa; Habib Ur Rehman (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the frequency of seroma formation in laparoscopic para-umbilical hernia repair with and without primary closure of defect. Method: The randomised parallel group study was conducted at the Department of Surgery, Bahawal Victoria Hospital, Bahawalpur, Pakistan, from October 1, 2019, to May 31, 2020, and comprised patients of both genders age 25-65 years diagnosed as a case of para-umbilical hernia. The patients were randomised into group A which subsequently had laparoscopic primary repair of defect with non-absorbable suture prior to mesh placement, and group B which had laparoscopic repair without primary closure of the defect. Case sheets of patients were prepared for age, gender, duration of disease, operating time, body mass index and the presence or absence of seroma formation. Data was analysed using SPSS 20. Results: Of the 100 patients, 35(35%) were males and 65(65%) were females with male-to-female ratio of 1:1.9, and an overall mean age of 43.92±10.77 years. Both groups had 50(50%) patients each. . Post-operative seroma formation was noted in 1(2%) group A patient and 12(24%) group B patients (p=0.001). Conclusion: Primary closure of the fascial defect in laparoscopic para-umbilical hernia repair resulted in decreased frequency of post-operative seroma formation. Key Words: Paraumbilical hernia, Seroma, Laparoscopic paraumbilical hernia repair.